New Aspects of Phloem-Mediated Long-Distance Lipid Signaling in Plants - Benning, Urs F.; Tamot, Banita; Guelette, Brandon S.; Hoffmann-Benning, Susanne (Frontiers in Plant Science, 2012)
Plants are sessile and cannot move to appropriate hiding places or feeding grounds to escape adverse conditions. As a consequence, they evolved mechanisms to detect changes in their environment, communicate these to different organs, and adjust development accordingly. These adaptations include two long-distance transport systems which are essential in plants: the xylem and the phloem. The phloem serves as a major trafficking pathway for assimilates, viruses, RNA, plant hormones, metabolites, and proteins with functions ranging from synthesis to metabolism to signaling. The study of signaling compounds within the phloem is essential for our understanding of plant communication of environmental cues. Determining the nature of signals and the mechanisms by which they are communicated through the phloem will lead to a more complete understanding of plant development and plant responses to stress. In our analysis of Arabidopsis phloem exudates, we had identified several lipid-binding proteins as well as fatty acids and lipids. The latter are not typically expected in the aqueous environment of sieve elements. Hence, lipid transport in the phloem has been given little attention until now. Long-distance transport of hydrophobic compounds in an aqueous system is not without precedence in biological systems: a variety of lipids is found in human blood and are often bound to proteins. Some lipid-protein complexes are transported to other tissues for storage, use, modification, or degradation, others serve as messengers and modulate transcription factor activity. By simple analogy it raises the possibility that lipids and the respective lipid-binding proteins in the phloem serve similar functions in plants and play an important role in stress and developmental signaling. Here, we introduce the lipid-binding proteins and the lipids we found in the phloem and discuss the possibility that they may play an important role in developmental and stress signaling.